Study on the effect of seasonal variation on expression of serum biochemicals in pigs - BORAH, S; SOREN, S; TALUKDAR, R; GOGOI, J; CHAKRABORTY, S; SAIKIA, K; BORDOLOI, G; BHATTACHARRYA, B N; BARUAH, A; TAMULI, U R (The Indian Journal of Animal Sciences, 2021)
Pigs are particularly susceptible to heat stress because of their more sub-cutaneous fat with little or non-functional sweat glands. Pigs depend on panting as primary mechanism of heat dissipation and/or wallowing. Therefore, a study was conducted to generate basic information on certain blood biochemicals of pigs reared in high humid climatic condition. For the purpose, blood samples were collected randomly from 400 female pigs (6–12 month of age) during summer and winter of the year. The analysis of THI has shown an increase in the study area since 2012 to 2018. The hematological study of the pigs revealed a variation in respect of Hb and TEC with the season. Estimation of different enzymes showed increase with the increase of THI. The activity of enzyme, hormones except leptin was accelerated. Expression of IGF 1, HSP 70 and HSP 90 was also affected with the change of THI. The level of Kisspeptin and FSH β receptor showed difference between two seasons of the year. However, the level of Kisspeptin and FSH β receptor in serum of the experimental animals was found to be insufficient to initiate puberty till 12 months of age. It can be concluded that the pigs reared in semi-intensive system under high humid climatic condition did not attain puberty up to one year of age.